El código de comercio y las actividades comerciales que realizan los menores de edad - CARRIÓN PACHECO, YESSENIA MARIBEL (2016)
Constitutionally, minors are entitled to the state to protect against labor exploitation, from forced, heavy and tiring work; which it is harmful to their health or physical, mental, spiritual, moral or social development, or that could hinder the exercise of their right to education. The reality differ much, for children and adolescents who work as employees or independently; especially selling or marketing various products; without the state, centralized or decentralized, solve this problem. The Constitution of the Republic of Ecuador, said: “Article 46. The State shall, inter alia, the following measures to ensure the children and teenagers. ... 2. Special protection against any type of labor exploitation. Work under fifteen is prohibited, and political progressive elimination of child labor will be implemented. The work of adolescents and adolescents will be exceptional and may not violate their right to education or made in harmful or dangerous situations for their health or personal development. It will respect, recognize and support their work and other activities provided they do not conflict with their education and their development ... "But the truth is that children and adolescents currently do business, not exceptionally but frequently. Part of the problem arises from the rules contained in the Code for Children and Adolescents, which states: "Art. 82. It is fixed at fifteen years as the minimum age for all types of work, including domestic service, with the exceptions under this Code, more laws and international legally binding instruments in the country" Clearly, according to this legal body, the work of adolescents do not enjoy exceptional, so lower from 15 years can make or be required to perform work activities, leaving aside other own occupations of their developmental stage and is the right to education, without the State do the follow-up. The Commercial Code, states in Article 1: "The Commercial Code governs the obligations of traders in their business operations and acts and contracts of trade, whether implemented by non-traders" Then forth in Article 2 "These are traders who, having capacity to contract, make trade their usual profession". And with respect to children, it is used as matching or supplementary to the Civil Code Act, saying the article6 that: "Any person who, under the provisions of the Civil Code, has the capacity to contract, the also have to engage in commerce". That is, from the perspective of the Commercial Code, the work or commercial activities of minors, it is a simple legal institution of "capacity to contract" reduce, and is not seen as a more complex problem in greater depth, as does the Code of Childhood and Adolescence, normative should reform the Code of Commerce.